The Effects of interruption on multi-tasking in healthy adults - Hough, Emily (My University, 2006)
Multitasking is a skill that is essential for effective everyday living. However, despite an increase in attempts to identify the cognitive components underlying such a skill, there is still uncertainty over the exact processes involved and what might impair them. This research has examined the effects of interruptions on a novel multitasking task (MT) and a single task (ST), in an attempt to further understand the processes involved. 40 participants completed both a ST and the MT, and were interrupted with a one minute arithmetic task during each. The novel MT required participants to complete subgroups from each of the four tasks provided (tangled lines, visual search, telephone and LegoTM) over ten minutes. The ST required participants to perform only one of the four tasks for the full ten minutes. Participants’ working memory scores were also measured. Interruption effects did not differ between the ST and the MT, and the interruption was not found to disrupt task performance. Strong effects of memory for task instructions were also found. It is suggested that participants adopted a strategy for use during the MT, with different strategies chosen by those with high and low working memory scores. These results are considered in relation to previous research, and appear to support the suggestion that the ability to deal with an unexpected interruption is separate from the ability to complete either a multitasking task or a single task (Law et al., 2004). The limitations surrounding this study are also considered, as is the need for future research that continues to develop models of multitasking, and methodologies for investigating the cognitive processes involved as well as what might impair them.
Keywords: multi-tasking; multi-tasking Task (MT); single task (ST); Interruption effects